Children with classic congenital adrenal hyperplasia experience salt loss and hypoglycemia: evaluation of adrenal crises during the first 6 years of life. Issue 2 (February 2016) - Odenwald, Brigitte; Nennstiel-Ratzel, Uta; Dörr, Helmuth-Günther; Schmidt, Heinrich; Wildner, Manfred; Bonfig, Walter
Abstract : Objective: To evaluate adrenal crises after the start of treatment up to the age of 6 years in children with classic congenital adrenal hyperplasia (CAH). Design: Analysis of data extracted from a population-based prospective long-term follow-up study of children detected in neonatal screening. Methods: Data of 102 Bavarian children with classic CAH due to 21-hydroxylase deficiency were analyzed, using parental questionnaires and medical reports. Parent-reported hospital admissions of children diagnosed with acute health impairment were included in the analysis if salt loss (hyponatremia) or hypoglycemia was documented in the discharge summary. Results: A total of 74 children (72.5%) had no report of hospital admissions with salt loss or hypoglycemia during the observational period. However, in 27.5% of the children, 22 salt-wasting crises (seven of these also with low blood glucose) and 16 hypoglycemic episodes without salt loss were reported. Furthermore, the cumulative incidence for seizures was elevated; 13 children experienced seizures during hyponatremia or hypoglycemia. Most adrenal crises were triggered by infections, often with inappropriate emergency management, but in 11 cases hypoglycemia occurred unexpectedly, without evidence of severe illness and without any management errors. Frequency of adrenal crises was 6.5 per 100 patient years (95% CI: 4.6–8.8). Conclusions: Crisis prevention remains a permanent challenge for families and physicians caring for children with classic CAH. Expert care and compliance with emergency recommendations are crucial. Further research on the interactions among glucocorticoid deficiency, adrenomedullary dysfunction, and glucose metabolism is necessary for the prevention of hypoglycemia, especially in young CAH patients.